Transformation in Bacillus subtilis: a 75,000-dalton protein complex is involved in binding and entry of donor DNA. - Smith, H (1984)
A 75,000-dalton protein complex involved in DNA binding during transformation was purified from membranes of competent Bacillus subtilis cells. Previous results (Smith et al., J. Bacteriol. 156:101-108, 1983) showed that the complex contained two polypeptides, polypeptide a (molecular weight, 18,000; isoelectric point, 5.0) and polypeptide b (molecular weight, 17,000; isoelectric point, 4.7) in approximately equal amounts. In the present experiments the two polypeptides were extracted from two-dimensional gels and studied separately and in combination with respect to DNA binding and nuclease activities. For DNA binding the interaction of both polypeptides was required. DNA binding occurred efficiently in the presence of EDTA. Nuclease activity was restricted to polypeptide b. The nucleolytic properties of b were identical to those of the native 75,000-dalton complex. Polypeptide a affected b by reducing its nuclease activity. Analysis of the nuclease subunit b on DNA-containing polyacrylamide gels revealed nuclease activities at four different molecular weight positions. These activities were identical to the major competence-specific nuclease activities which were previously implicated in the entry of donor DNA during transformation (Mulder and Venema, J. Bacteriol. 152:166-174, 1982). These results indicate that the 75,000-dalton protein complex is composed of two different competence-specific polypeptides involved in both binding and entry of donor DNA. The possible roles of the two polypeptides in the transformation of B. subtilis are discussed.